مباحث أبي عبيدة البالغية في كتابه "مجاز القرآن" - رعد رفعت محمد/ أستاذ مساعد دكتور (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Abu Obeida’s book "The Miracle of the Qur’an" became a fertile material for linguistic and religious research. I chose the rhetorical side to study the book and the methodology of its author. The research is entitled: Abi Ubaydah’s rhetorical research in his book "Majaz al-Qur’aan". The nature of the study necessitated dividing it into three sections, preceded by prefabricating and sealing it with recommendations, and finally a list of sources and references adopted by the research. In his book, Abu Obeida deposited his linguistic knowledge in a manner of eloquence, eloquence, and the totality of his theoretical views, in order to serve the Qur’anic text in an analysis and understanding of the meaning through the eloquence of the Qur’an. My dependence on the study was as follows: (A) The inductive approach, following the scientific material, collecting it and examining it for study. B - descriptive approach, the interpretation of phenomena and statement and striking examples. (C) Analytical approach, by analyzing the scientific material, revealing its implications, and evaluating it if necessary.